Управление рисками в гибких методологиях разработки ПО - Жилина, Е. Ю. (ХНУРЕ, 2011)
The success of any project depends on how much time and how much it is released. Achieving this task is associated with risks, so it is important to monitor and manage them throughout the project life cycle
Keywords: управление рисками; разработка ПО